Transthyretin gene mutations in British and French patients with amyloid neuropathy. Issue 6 (June 1993) - Bhatia, K; Reilly, M; Adams, D; Davis, M B; Hawkes, C H; Thomas, P K; Said, G; Harding, A E
Abstract : Five patients, two British and three French, with late onset amyloid neuropathy were found to have mutations of the transthyretin (TTR) gene associated with the Portuguese and German types of familial amyloid polyneuropathy. Familial amyloid polyneuropathy is rare in the United Kingdom and has not previously been defined at a molecular genetic level. None of the patients had a history of affected antecedents; the role of TTR gene analysis in diagnosing known or suspected amyloid neuropathy, regardless of family history or ethnic background, is emphasised.